SHARIA COMPLIANCE IN THE USE OF COLLATERAL FOR RISK MITIGATION IN MURABAHAH FINANCING: A CASE STUDY OF COOPERATIVE SYIRKAH BERKAH BERSAMA SIDOARJO - Wibowo, Endro (Universitas Muhammadiyah Surabaya, 2025)
One of the biggest and most feared risks in murabahah financing is default risk. To mitigate the default risk, Islamic Financial Institutions usually require collateral as a condition for financing approval. Koperasi Syirkah Berkah Bersama (KSBB) Sidoarjo started the process of becoming an Islamic financial institution that can provide murabahah financing to its members while maintaining sharia compliance. One of KSBB's efforts to mitigate the risk of default and ensure sharia compliance in murabahah financing is through the use of collateral in murabahah financing. The purpose of this research is to understand the implementation of collateral in murabahah financing and the analysis of sharia compliance in that implementation as a form of mitigating the risk of default. This research method is a qualitative research methodology with a case study approach with descriptive qualitative data analysis. The research data processed in this research comes from informant interviews and various relevant documents related to guarantees in murabahah financing and then analyzed and compared with existing theories or fatwas. The results of this research show that the implementation of guarantees in murabahah financing has met sharia compliance, in accordance with the fatwa decrees of DSN MUI and AAOIFI.